Usaha Durian di Desa Barung-barung Balantai Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan Tahun 2012 - 2024 - Salsabila, Ahada; Najmi, Najmi (Jurusan Sejarah FIS UNP, 2025)
Durian (Durio zibethinus Murr.) is an exotic tropical fruit plant with a distinctive taste and aroma. This fruit is known as the